Edukasi pencegahan Coronavirus Disease (COVID-19) di Panti Asuhan Al-Fatih Palembang - Razak, Rahmatiilah; Budiastuti, Anggun; Sunarsih, Elvi; Ardillah, Yustini (Fakultas Kedokteran Universitas Sriwijaya, 2023)
COVID-19 remains the focus of public health, both global and national. The continuous increase in COVID-19 cases indicates the need for efforts to improve health protocols in the community. This community service was held in September 2021 at the Al-Fatih Orphanage in Palembang, with 17 orphanage children as the target population. This community service activity uses the counseling method. Pre and post-tests were used to measure knowledge before and after counseling about coronavirus disease and its transmission. Based on the paired t-test analysis, the p-value=0.0001 (<0.05), so it can be concluded that there was a significant difference in knowledge before and after educating the public about efforts to prevent COVID-19.